INNV-04. PRIMARY TREATMENT OF SMALL-TO-MEDIUM(< 3CM) SPORADIC VESTIBULAR SCHWANNOMAS: SYSTEMATIC REVIEW & META-ANALYSIS (2010 TO 2020). (14th November 2022) - Savardekar, Amey; Terrell, Danielle; LeLe, Saudamini; Kosty, Jennifer; Wang, Chiachien Jake; Guthikonda, Bharat
Abstract: INTRODUCTION: Over the past two decades, the treatment of small-to-medium (< 3cm) sporadic vestibular schwannomas (VS) has experienced a definite shift to stereotactic radiosurgery vis-a-vis microsurgery. We performed a systematic review and meta-analysis of VS patients primarily treated with stereotactic radiosurgery (SRS) or microsurgery (MS), with particular attention to hearing preservation outcomes (HPO), tumor control (TC), and facial nerve dysfunction (FND). Materials and METHODS: A systematic review was conducted (Medline database) for the period, 2010 to 2020. Studies with mean/median follow-up of >/= 3 years were included. Studies had to report an acceptable standardized hearing metric. HPO, TC, and treatment complications (with special attention to FND) were compared between the MS and SRS groups. RESULTS: Thirty-two studies met our inclusion criteria: 10 for microsurgery and 23 for radiosurgery (one comparative study included in both arms). HPO were comparable between MS group and SRS group (56% and 59%, p=0.1527). TC was significantly better in MS group (98%) versus SRS group (92%) [p < 0.0001]. FND was significantly higher in MS group (11%) versus SRS group (2%) [p < 0.0001]. CONCLUSION: The ability to diagnose small sporadic VS earlier, allows patients time to consider all possible treatment options which include observation, radiosurgery, or microsurgery. The data presented in this study will assist physicians in their ability to appropriately counsel patients on the benefits and risks of both treatment modalities with the most recent evidence on the factors that contribute greatly to patients' quality of life: HPO, TC and FND.